Nanometer silica film three-layer stacked solar cell and preparation method thereof - CHENG GUANGGUI; HE YULIANG; YUAN NINGYI; WANG XIUQIN; DING JIANNING (2011)
The invention relates to a film solar cell and a preparation method thereof, in particular to a nanometer silica film three-layer stacked solar cell and a preparation method thereof. The method of plasma enhanced chemical vapor deposition (PECVD) is adopted for preparing a hydrogenated nanometer silica film (nc-Si:H). An nc-Si:H/nc-Si:H/nc-Si:H film three-layer stacked solar cell is prepared on asoft metal or polyimide film substrate. The top cell, the middle cell and the bottom cell adopt the N<+>NIPP<+> structure. The method of radio frequency sputtering is adopted for depositing an Al/AlxZn[1-x]O double-layer back electrode and an AlxZn[1-x]O film upper electrode. The invention avoids the use of amorphous silicon and expensive amorphous germanium silicon; the relatively thinner nanometer silica film three-layer stacked solar cell with high efficiency and stability is obtained on the soft substrate by taking advantage of the adjustable scope of the band gap of nanometer silica width, the relatively higher a